Innovation of Efficient Seaweed Drying Equipment for Borongloe Village, Pajukukkang District, Bantaeng Regency - Abu Libda, Imran; Soraya, Andi Inayah (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2024)
This study presents the development and implementation of an innovative seaweed drying tool specifically designed for the residents of Desa Borongloe, Kec. Pajukukkang, Kab. Bantaeng. Seaweed farming is a critical economic activity in this region, yet traditional drying methods are inefficient, time-consuming, and heavily reliant on favorable weather conditions, often resulting in inconsistent product quality. To address these challenges, an efficient drying tool was designed, constructed, and introduced to local farmers. The implementation of this tool showed a significant reduction in drying time, improved quality of the dried seaweed, and increased income for the farmers. This journal discusses the project's planning, execution, results, and future recommendations for sustainable adoption and scalability.